2021
DOI: 10.1097/jcp.0000000000001475
|View full text |Cite
|
Sign up to set email alerts
|

Association of Optimal Lamotrigine Serum Levels and Therapeutic Efficacy in Mood Disorders

Abstract: Purpose:The aim of the study was to appraise the current evidence on the optimal serum level for lamotrigine (LAM) in the treatment of mood disorders (major depressive disorder, bipolar disorder).Methods: Major databases were searched for randomized controlled trials, open-label trials, and observational studies reporting serum LAM levels in adult patients treated with LAM for mood disorders.Results: A total of 814 abstracts were screened and 24 articles were selected for full-text review. Seven studies (226 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…21 Serum levels of LTG would be needed for the accurate examination of the efficacy of LTG. 22 In addition, the rash was not diagnosed by a dermatologist in this study, and causes other than LTG were not excluded, which may have led to overdiagnosis. 23 Furthermore, the definition of slow titration used in this study is comprehensive, and schedules with fewer initial doses that used the standard titration interval could not be distinguished from those that used prolonged intervals with the standard titration dosing.…”
Section: Limitationsmentioning
confidence: 89%
“…21 Serum levels of LTG would be needed for the accurate examination of the efficacy of LTG. 22 In addition, the rash was not diagnosed by a dermatologist in this study, and causes other than LTG were not excluded, which may have led to overdiagnosis. 23 Furthermore, the definition of slow titration used in this study is comprehensive, and schedules with fewer initial doses that used the standard titration interval could not be distinguished from those that used prolonged intervals with the standard titration dosing.…”
Section: Limitationsmentioning
confidence: 89%
“…Monitoring for adverse effects needs to include baseline and periodic assessment for symptoms and signs of thyrotoxicosis (palpitations/tachycardia, hand tremors, anxiety, insomnia, unintentional weight loss, oligo/amenorrhea, fragility fractures/low bone density) [ 21 ]. Long-term supratherapeutic TH augmentation, especially in postmenopausal women with reduced physical activity, a personal history of cigarette smoking, an excessive history of serotonergic antidepressant exposure, a family history of osteoporosis, and advanced age is associated with high risk for fragility fractures and osteoporosis [ 27 ]. T4 is often started at 50 mcg per day and optimized to 100–150 mcg per day [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias was assessed for random sequence generation, allocation concealment, the blinding of participants and personnel, the blinding of outcome assessment, incomplete outcome data, selective reporting, and other biases. For open-label non-randomized studies/observation studies, we used the Methodological Index for Non-Randomized Studies [ 26 , 27 ]. Quantitative tests to assess publication bias were not performed due to the limited number of studies.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review conducted in an adult population underscored the clinical recommendation for using LAM serum levels to target clinical efficacy in adult mood disorders. This review suggested that it is reasonable to obtain serum levels for LAM and consider an optimization to a minimum level of 3 μg/mL (0.003 kg/m 3 ) of LAM in adults 25 …”
Section: Discussionmentioning
confidence: 99%
“…This review suggested that it is reasonable to obtain serum levels for LAM and consider an optimization to a minimum level of 3 μg/mL (0.003 kg/m 3 ) of LAM in adults. 25 To date, no study has been conducted to review the evidence for effective serum levels of LAM treatment of PMD. Therefore, future RCTs should consider including therapeutic drug monitoring in PMD.…”
Section: Discussionmentioning
confidence: 99%